2002
DOI: 10.1175/1520-0493(2002)130<1830:aomhfs>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

An Operational Multiscale Hurricane Forecasting System

Abstract: The Operational Multiscale Environment model with Grid Adaptivity (OMEGA) is an atmospheric simulation system that links the latest methods in computational fluid dynamics and high-resolution gridding technologies with numerical weather prediction. In the fall of 1999, OMEGA was used for the first time to examine the structure and evolution of a hurricane (Floyd, 1999). The first simulation of Floyd was conducted in an operational forecast mode; additional simulations exploiting both the static as well as the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 42 publications
0
30
0
Order By: Relevance
“…Atmospheric models have also been developed using unstructured triangular and pentagonal-hexagonal grids (e.g. Bacon et al, 2000;Gopalakrishnan et al, 2002;Ford et al, 2004a,b;Pain et al, 2005;Piggott et al, 2005;LĂ€uter et al, 2007;Weller and Weller, 2008;Bernard et al, 2009b;Weller et al, 2009Weller et al, , 2010Ringler et al, 2011) and are similar in many ways to those for oceanic applications. An important virtue of unstructured grids is their ability to match a grid to awkward-shaped boundaries, such as the land boundaries of oceanic models.…”
Section: Scope Of the Review And Outlinementioning
confidence: 99%
“…Atmospheric models have also been developed using unstructured triangular and pentagonal-hexagonal grids (e.g. Bacon et al, 2000;Gopalakrishnan et al, 2002;Ford et al, 2004a,b;Pain et al, 2005;Piggott et al, 2005;LĂ€uter et al, 2007;Weller and Weller, 2008;Bernard et al, 2009b;Weller et al, 2009Weller et al, , 2010Ringler et al, 2011) and are similar in many ways to those for oceanic applications. An important virtue of unstructured grids is their ability to match a grid to awkward-shaped boundaries, such as the land boundaries of oceanic models.…”
Section: Scope Of the Review And Outlinementioning
confidence: 99%
“…A complete description of OMEGA can be found in BACON et al (2000), while the details of the model validation studies can be found in BOYBEYI et al (2001) and GOPALAKRISHNAN et al (2002). OMEGA is a fully non-hydrostatic, three-dimensional prognostic model based on an adaptive, unstructured triangular prism grid that is referenced to a rotating Cartesian coordinate system.…”
Section: Description Of the Forecast Model Targeted Observations Anmentioning
confidence: 99%
“…For example, BACON et al (2000) have used unstructured meshes with both static and dynamic grid adaptation for atmospheric modeling in a fully compressible and nonhydrostatic model -the Operational Multiscale Environment model with Grid Adaptivity (OMEGA). The OMEGA model is based on unstructured prisms and has been applied to many atmospheric problems and validated extensively (e.g., BOYBEYI et al, 2001;GOPALAKRISHNAN et al, 2002). SARMA et al (1999) have demonstrated significant improvement in solution accuracy by using dynamic grid adaptation for predicting chemical plume concentrations.…”
Section: Unstructured Gridsmentioning
confidence: 99%
“…Solution-adaptive techniques (i.e., dynamic grid adaptation) can also be implemented with relative ease to improve the solution by dynamically adapting the mesh to evolving physical features. Solution-adaptive methods can be helpful, for example, in predicting the trajectory of hazardous materials (AHMAD et al, 1998;SARMA et al, 1999;GHORAI et al, 2000), simulations of convective weather systems such as squall lines and mesoscale convective complexes, and for tracking hurricanes (GOPALAKRISHNAN et al, 2002).…”
Section: Introductionmentioning
confidence: 99%